Long-term Outcome of Surgical Treatment for Late Intraocular Lens Dislocation Associated With High Intraocular Pressure: A Case Series. Issue 9 (September 2017) - Torres, Lucas A.; Vianna, Jayme R.; Nicolela, Marcelo T.
Abstract : Purpose: To demonstrate the long-term safety and efficacy of transscleral intraocular lens (IOL) fixation combined with an Ahmed glaucoma drainage device implantation for patients with late IOL dislocation and high intraocular pressure (IOP). Methods: This is a retrospective report of a series of patients who underwent this combined surgery. The main outcome variables studied were change in visual acuity (VA), IOP, and number of medications compared with preoperative levels. Surgical failure was defined as a decrease in VA of at least 3 Snellen lines, IOP above 20 mm Hg or IOP reduction <25% from preoperative levels at ≥2 consecutive visits, at least 2 months apart. Results: Eleven patients with median age of 83 years (range, 77 to 92 y) were included in the study. All patients had a previous diagnosis of pseudoexfoliation. After a median follow-up time of 1.75 years (range, 0.83 to 2.5 y), the median IOP decreased from 33 mm Hg (range, 24 to 47 mm Hg) to 13 mm Hg (range, 5 to 16 mm Hg; P <0.01). The number of glaucoma medications also decreased from 3 (range, 1 to 4) to 2 (range, 0 to 4; P =0.03). The median log MAR VA improved from 0.77 (range, 0.3 to 2) preoperatively to 0.44 (range, 0 to 3) postoperatively ( P =0.27). Four patients had postoperatory surgical complications: choroidal effusion (2), vitreous hemorrhage and hyphema (1), vertical diplopia (1). The survival probability over 2.5 years was 90.9% (confidence interval, 75.4%-100%). Conclusion: Transscleral IOL fixation associated with Ahmed glaucoma drainage device implantation is a safe and effective surgical option for patients with late IOL dislocation and elevated IOP.